Prevalence and risk factors for HBV, HCV and HDV infections among injecting drug users from Rio de Janeiro, Brazil - Oliveira,M.L.A. (1999)
Viral hepatitis constitutes a major health issue, with high prevalence among injecting drug users (IDUs). The present study assessed the prevalence and risk determinants for hepatitis B, C and D viruses (HBV, HCV and HDV) infections among 102 IDUs from Rio de Janeiro, Brazil. Serological markers and HCV-RNA were detected by enzyme immunoassay and nested PCR, respectively. HCV genotyping was determined by restriction fragment length polymorphism analysis (RFLP). HBsAg, anti-HBc and anti-HBs were found in 7.8, 55.8 and 24.7% of IDUs, respectively. In the final logistic regression, HBV infection was independently associated with male homosexual intercourse within the last 5 years (odds ratio (OR) 3.1; 95% confidence interval (CI) 1.1-8.8). No subject presented anti-delta (anti-HD). Anti-HCV was detected in 69.6% of subjects, and was found to be independently associated with needle sharing in the last 6 months (OR 3.4; 95% CI 1.3-9.2) and with longer duration of iv drug use (OR 3.1; 95% CI 1.1-8.7). These data demonstrate that this population is at high risk for both HBV and HCV infection. Among IDUs from Rio de Janeiro, unprotected sexual intercourse seems to be more closely associated with HBV infection, whereas HCV is positively correlated with high risk injecting behavior. Comprehensive public health interventions targeting this population and their sexual partners must be encouraged.